Neuroprotective effects of metformin on cerebral ischemia‐reperfusion injury by regulating PI3K/Akt pathway - Cailian Ruan; Hongtao Guo; Jiaqi Gao; Yiwei Wang; Zhiyong Liu; Jinyi Yan; Xiaoji Li; Haixia Lv (Brain and Behavior, 2021)
Abstract Metformin (Met) is a commonly used drug in the treatment of type 2 diabetes. Currently, it has been found that Met can effectively reduce the incidence of stroke and exert anti‐inflammatory effects. However, its role in ischemia‐reperfusion (I/R)‐induced nerve injury remains unclear. This study aims to investigate the neuroprotective effects of Met in I/R‐induced neuron injury as well as the underlying mechanism. A middle cerebral artery occlusion (MCAO) model was established in Sprague Dawley (SD) rats, which were then treated with different doses of Met. Neurological deficits of rats were measured at different times post‐surgery. TTC staining was done to observe the volume of cerebral infarction. HE staining was performed to observe pathological changes of brain tissues. Immunohistochemistry was performed to observe the expression of inflammatory factors in the cerebral tissues. qRT‐PCR method was used to detect the relative expression of PI3K, Akt mRNA in cells after 24 h of drug action. Western blot method was used to detect the expression of PI3K, p‐PI3K, Akt, and p‐Akt in hippocampus. What is more, in vitro experiments were performed on BV2 microglia to verify the role of Met against oxygen‐glucose deprivation (OGD). As a result, Met dose‐dependently attenuated neurological deficits and neuronal apoptosis. Besides, Met administration also significantly reduced BV2 cells apoptosis and inflammatory response. Mechanistically, Met inactivated PI3K/Akt pathway induced by I/R and OGD, while it upregulated PI3K. In conclusion, Met protected rats from cerebral I/R injury via reducing neuronal apoptosis and microglial inflammation through PI3K/Akt pathway.